Scratch resistance of a polycarbonate + organoclay nanohybrid (eXPRESS Polymer Letters, 2009)
A polycarbonate-based nanohybrid has been created containing 1 wt% of Bentone 2010, an organically modified montmorillonite. A micro-section on the nanohybrid obtained using focused ion beam (FIB) and field emission scanning electron microscopy (FESEM) was employed to observe the orientation of the nanoclay inside a polycarbonate (PC) matrix in the cross-section FIB-milled face. A micro-scratch tester was used to measure the scratch resistance in terms of residual (healing) depth Rh under progressive load and in sliding wear. Effects of the number of scratches, normal load and scratch velocity have been evaluated as a function of nanoclay orientation. In sliding wear (multiple scratching along the same groove), our nanohybrid reaches residual depth values that remain constant after a certain number of scratches, a manifestation of strain hardening. The number of scratches to induce strain hardening decreases as the normal applied load increases. SEM was used to characterize deformation and wear mechanisms that operate on contacts and the results related to the wear data.